2019
DOI: 10.1017/s1478951519000853
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caregiver burden for mothers of children undergoing Acute Lymphocytic Leukemia (ALL) treatment

Abstract: Objective The present study examined the extent to which social support (SS) availability and satisfaction could predict the extent of caregiver burden (CB) among mothers of children with Acute Lymphocytic Leukemia (ALL). Method The study was a cross-sectional, descriptive-correlative study. It was conducted on a sample of 117 mothers whose children were undergoing treatment in a public hospital in Bam, Iran. The Norbeck Social Support Scale and the Caregiver Burden Scale were used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
(68 reference statements)
3
15
1
5
Order By: Relevance
“…Single caregivers had less care burden than married caregivers. Contrary to the current study, the results of a study (2019) in Iran showed that married mothers had less care burden than single mothers [ 16 ]. Moreover, two studies in the Netherlands (2014) and Canada (2012) showed single mothers had high care burden [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Single caregivers had less care burden than married caregivers. Contrary to the current study, the results of a study (2019) in Iran showed that married mothers had less care burden than single mothers [ 16 ]. Moreover, two studies in the Netherlands (2014) and Canada (2012) showed single mothers had high care burden [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 91%
“…In line with a previous study [ 14 ], the results showed that caregivers with high education level experienced less care burden than caregivers with low education level. However, some studies have indicated no relationship between education and care burden [ 16 ]. Those who are more educated may be better able to manage their stress and have more problem-solving skills [ 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiver burden is a complex construct that depends heavily on the context and culture of the community in which care takes place [ 10 ]. There are several definitions of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature, caring for children with diabetes is a very difficult task. Mothers are the primary caregivers in most countries, especially in the middle eastern ones and cultures [ 10 , 18 ]. Most mothers and families accept the disease eventually but in different paths.…”
Section: Introductionmentioning
confidence: 99%